Schematic model of two hard cores for cold fission - Montoya, Modesto (1990)
Structures in mass and total kinetic energy distribution (TKE) in cold fission of U-234, U-236, and Pu-240 are interpreted in terms of a static scission configuration model. The role of shells in fragments present in their deformation energy function, in the Coulomb interaction energy between fragments at scission (C), and in the available energy (Q) are studied in detail. The maximal value of Cmax, corresponding to the most compact scission configuration, is calculated for several mass fragmentations. It is shown for a given primary fragmentation and Q being constant, that, if one increases the charge asymmetry, Cmax will increase. This dependence produces oscillations of Cmax as a function of light fragment mass (AL) which are correlated with the observed oscillations of the maximal values of TKE, TKEmax. The calculated Cmax values show odd-even effects in contrary to the experimental smooth TKEmax -lines. A schematic approach, in terms of two hard cores and a certain number of orbiting nucleons during the process of fission, is used to calculated odd-even effects in proton and neutron number distributions and in the fragment kinetic energy as a function of fragment charge. One assumes that pair breaking occurs between saddle and scission. A small fraction of total fission events ends up in paired states in both fragments.